The Apostolic tradition reconstructed: a text for students - Bradshaw, Paul F. (Joint liturgical studies, 2021)
This reconstruction of the anonymous and untitled ancient church order that was formerly imagined to have been the Apostolic Tradition of Hippolytus is distinctive from other modern editions of it in two ways. First, it draws on an early Ethiopic translation of the missing original Greek text that was only published in full as recently as 2011 by Alessandro Bausi and, except where there is a surviving passage in Greek, employs it exclusively to fill in the gaps in the incomplete early Latin version, rather than the much later Coptic, Arabic, and Ethiopic translations that had to be used prior to that. This has resulted in some significantly different readings. Secondly, it displays what are judged to have been successive chronological layers within the church order in a more visual manner by the use of distinctive typefaces for each of these strata from the second century to the early part of the fourth century, and it accompanies the translation with explanatory notes designed to help the newcomer understand better the evolution of the text